Lupin III [videorecording (DVD)] : the first - Yamazaki, Takashi, 1964-; Yamazaki, Takashi, 1964-; Sinterniklaas, Michael; Sinterniklaas, Michael; Monkī Panchi, 1937- (GKids, 2021)
Lupin and his partners set out to find the mysterious Bresson diary before it falls into the hand of an evil underworld cult.